FACTORS ASSOCIATED WITH TIME TAKEN TO PRESENT TO THE HOSPITAL WITH ACUTE BOWEL OBSTRUCTION: PARIRENYATWA, ZIMBABWE. - Rutsito, Locadia; Mugadza, Gladys; Kapfunde, Abigail; Rukweza, Judith; Ndaimani, Augustine (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2017)
Tittle of the study: Factors associated with time taken to present to the hospital amongpatients aged 20 to 40 years with acute bowel obstruction admitted in Parirenyatwa surgicalwards.Introduction: Acute small bowel obstruction is a common surgical emergency whichconstitutes a major cause of morbidity and financial expenditure in hospitals around theworld and a significant cause of admissions to emergency surgical departments. Themanagement method of bowel obstruction and success of the management is among otherfactors determined by the time taken to present to the hospital .It has been shown that thosepatients who present to the hospital within 24 hours from onset of symptoms have highmanagement success rate.Aim: This research study aimed at determining the factors associated with the time taken topresent to hospital among patients aged 20 to 40 years with acute small bowel obstruction inParirenyatwa General Surgical WardsMethodology: This study utilized a quantitative, descriptive, non-experimental design. 30participants were conveniently selected from an accessible population of men and womenwith acute small bowel obstruction aged 20 to 40 years admitted in PGH general surgicalwards. Data was analysed using SPSS.Results: A total of 30 patients with acute small bowel obstruction participated in thisresearch. Two (6.7%) of the participants had prior knowledge about bowel obstruction amajority (93.3%) had no knowledge about the disease till they got sick. A lager number of theparticipants (70%) presented late between 2 to 10 days. Lack of finance was one of thecontributing factor to late presentation as expressed by (20%) of the participants.Conclusion: From this study, lack of knowledge, lack of finances and long distance to thehealth care facilities were the leading causes of delays in seeking medical care in acute smallbowel obstruction.